GARIS KEHIDUPAN ALAM SEMESTA - Rifqi Ardian, Ahmad
Universe, in general sense, is all of space and time which include things/objects that made life, either living-thing or inanimate object. The living-thing in universe is any individual entity that exhibits the properties of life; therefore they are the existence of life in earth. While inanimate object are space/astronomical objects or any lifeless object that moving, and therefore it can be found on earth as well. Both living-inanimate objects are brought this universe to life. Both had four dynamics : process, development, transformation, and diversification. Those four dynamics occurs continuously, and none of objects had exact same dynamics I, the writer, living in a relatively small place compared to whole universe : the city. In that city, writer dive and travel its space. Inside that, writer found same things as in universe occurs. From that experience, writer realizes the life of city mirroring the life of universe itself. This pushing the writer to realize of how the universe made its life. As an visual artist, the writer wants if the writer can made the most basic element of visual/every artworks : line, could “speak” about imagining various kind of life in this universe. From that, the writer expected these formalism-driven artwork could invite audience to imagine what universe might like; and this artwork also expected can be a facility for the writer to travel the formalism-based aesthetics and universe itself.